2009
DOI: 10.1111/j.1369-7625.2009.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

What, if anything, is specific about having a rare disorder? Patients’ judgements on being ill and being rare

Abstract: Background Growing efforts are made to improve the situation of persons with rare diseases, but the specific nature of these disorders remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
104
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(116 citation statements)
references
References 11 publications
4
104
0
8
Order By: Relevance
“…The condition of their disease being rare is not described or referred to as the most problematic element. A French study has pointed out how these patients do not perceive the aspect of rarity as the greatest source of difficulty, so long as they have found health professionals who are able to recognize their requirements (Huyard, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The condition of their disease being rare is not described or referred to as the most problematic element. A French study has pointed out how these patients do not perceive the aspect of rarity as the greatest source of difficulty, so long as they have found health professionals who are able to recognize their requirements (Huyard, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, the information patients find independently is not always understood, and if it is not accompanied by explanations, it can be disorientating. In literature, it is reported how often patients would like a guide to interpret the information they collect, expecting to receive explanations that they can understand (Huyard, 2009) The professional health care participants show as patient can have access to a mass of information which he is not able to select and it can lead to creating false expectations. They report how their approach is to propose that they can act as mediators, inviting the patient to discuss with them what they have found so that they can understand it better.…”
Section: Discussionmentioning
confidence: 99%
“…Patients report preferring and trusting their physician over all other sources of information about their conditions (14,15), but patients often report being frustrated with the lack of information provided by their physician and the lack of information about their conditions in general (9)(10)(11)(12)16). Even though patients prefer and trust their physicians, due to lack of information provision from their physicians, patients often turn to other sources, including the Internet, to find information about their conditions.…”
Section: Importance Of Health Information For Patients With Rare Disementioning
confidence: 93%
“…This study also found that rare disease patients' health care experiences would be improved if health care providers met what patients viewed as a moral expectation by providing diagnosis disclosure and providing information to the patient about the condition (11).…”
Section: Importance Of Health Information For Patients With Rare Disementioning
confidence: 95%
See 1 more Smart Citation